Comparison of Three Levels of Divorce in Whitfield County, State of Georgia, and the United States in Two Decades, 1990-2009 - Hassan A. El-Najjar (Journal of Public and Professional Sociology, 2015)
In this paper, there is an investigation of the North West Georgia divorce ratios in 1990-2010 and how they are related to the same ratios in the State of Georgia and the United States as a whole. The data showed that there was a decline in divorce ratios on the three levels. However, the North West Georgia divorce ratios were still much higher than the State and the national ratios. I would like to thank the three anonymous reviewers for their valuable suggestions.